PREPARATION OF STUDENTS FOR THE ORGANIZATION OF PROJECT- OF TECHNOLOGICAL ACTIVITY OF STUDENTS IN LESSONS OF LABOR TEACHING (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the difference of project and technological system from constructor and technological system and the ways of its organization in the higher educational establishment according to specialists training in the educational sphere named “Technology”.